Gospel Interpretation and the Q-Hypothesis. - Keith, Chris 1980-; Labahn, Michael 1964-; Müller, Mogens 1946-; Omerzu, Heike 1970- (London Bloomsbury Publishing PLC, 2018)
Cover -- Series -- Title -- Copyright -- Contents -- Preface -- List of Contributors -- Chapter 1 Introduction: What is at Stake by Advocating or Disputing the Two-Source Theory? -- Part I History and Theory -- Chapter 2 Conceptual Stakes in the Synoptic Problem -- 2.1 Methodological Issues -- 2.1.1 The Primary Data for the Synoptic Problem -- 2.1.2 Data, Inference and Editorial Scenarios -- 2.1.2.1 Describing the Data -- 2.1.2.2 Logical Inferences -- 2.1.2.3 Editorial Scenarios -- 2.2 Towards a Critical History of the Synoptic Problem -- 2.2.1 The Synoptic Problem and the Historical Jesus -- 2.2.2 The Conceptual Landscape of the Early Jesus Movement -- 2.2.3 Why Might This Matter? -- Chapter 3 Sad Sources: Observations from the History of Theology on the Origins and Contours of the Synoptic Problem -- 3.1 The Witness of the Gospels: Difference and Harmony from Luke to Augustine -- 3.1.1 From the Gospel to the Gospels -- 3.1.2 Legends about the Four Evangelists in the Early Church -- 3.1.3 Strategies to Counteract Confusion That Might be Caused by the Polyphony of the Gospels -- 3.1.3.1 Luke, Marcion and Tatian -- 3.1.3.2 Origen vs. Celsus -- 3.1.3.3 Augustine vs. Porphyry -- 3.2. From the Perspicuity (Klarheit) of Scripture to the Synoptic Problem -- 3.2.1 From Gospel Harmonies to the Perspicuity of Scripture -- 3.2.2 Ad Fontes -- 3.3 The Significance of the Wars of Religion for the Development of Christian Biblical Criticism -- 3.3.1 From the Perspicuity of Scripture to Clarity of Analysis -- 3.3.2 Disharmonization Strategies: Semler and Reimarus -- 3.3.3 Strategies of Reharmonization: The Griesbach Hypothesis and Eichhornâs âUr-Gospelâ Hypothesis -- 3.3.3.1 The Griesbach Hypothesis -- 3.3.3.2 The âUr-Gospelâ Hypothesis of Johann Gottfried Eichhorn -- 3.4 Afraid of the Myth: How the Two-Source Hypothesis Came into Being
3.5 Challenges and Insights from Reflection on the Historical Development of the Synoptic Problem: 10 Theses -- Chapter 4 Were the Gospel Authors Really âSimple Christians without Literary Giftâ (Albert Schweitzer)?: Arguments for the Ques -- 4.1 Introduction -- 4.2 From Urevangelium Hypothesis to the Mark Hypothesis -- 4.3 The Markan Hypothesis Is Supplemented by the Two-Source Hypothesis -- 4.4 Alternative Voices -- 4.5 Continuations of the Two-Source Hypothesis -- 4.6 Conclusion -- Chapter 5 Q and the Logia: On the Discovery and Marginalizing of P.Oxy.1 -- 5.1 Discovering the Logia -- 5.2 Interpreting the Logia -- 5.3 Competing Logia Theories -- 5.4 The Politics of Q -- Chapter 6 Watson, Q and âL/Mâ -- 6.1 Introduction: General Issues -- 6.2 Coincidences in Q? -- 6.2.1 Birth Narratives -- 6.2.2 Genealogies -- 6.2.3 Luke 3.1â20 -- 6.2.4 The Position of the Sermon on the Mount/Plain -- 6.3 Watson, Luke and the L/M Hypothesis -- 6.3.1 Order -- 6.3.2 âPlausibilityâ -- 6.3.3 Lukeâs Choice of Material -- 6.3.4 âMark-Q Overlapsâ -- 6.3.4.1 The Beelzebub Controversy -- 6.3.4.2 Mustard Seed -- 6.4 Conclusion -- Chapter 7 Seven Theses on the Synoptic Problem, in Disagreement with Christopher Tuckett -- 7.1 Thesis One: The âQâ hypothesis should not be regarded as a default position, to be assumed true unless and until proved false. -- 7.2 Thesis Two: In analysing evangelistsâ use of their sources, we may expect to find general tendencies but not rigid uniformity in their -- 7.3 Thesis Three: Evangelists may simultaneously both âagreeâ and âdisagreeâ with their sources. -- 7.4 Thesis Four: It would be an unlikely coincidence for two evangelists to make a series of parallel modifications to the same sources inde
7.5 Thesis Five: Source-critical hypotheses should focus on compositional process and not just on changes of wording. -- 7.6 Thesis Six: An evangelistâs modification to a source is best âexplainedâ by showing it to be an interpretative act. -- 7.7 Thesis Seven: There are more than three synoptic gospels for source-critical theories to take into account. -- Part II Textual Studies -- Chapter 8 Mark With and Against Q: The Earliest Gospel Narrative as a Counter-Model -- 8.1 Mapping Q and Mark in First Century CE Literary Activity -- 8.2 Q and Mark: Some Reflections about the State of the Art -- 8.3 Mark without Q: Resuming Desiderata -- 8.4 Mark with Q: Developing the Q Hypothesis -- 8.4.1 Markâs Knowledge of Q -- 8.4.2 Markâs Silence about the Q Movement and His Depiction of âOthersâ -- 8.4.3 Markâs Dealing with Q as a Literary Forerunner and/or Competitor -- Chapter 9 Refusing to Acknowledge the Immerser (Q 7.31â35) -- 9.1 Introduction -- 9.2 History of Interpretation -- 9.3 Analysis -- 9.3.1 Luke 7.31â35 -- 9.3.1.1 Groups of Children and Intergroup Relationships -- 9.3.1.2 Compatibility between the Parable and Its Interpretation -- 9.3.1.3 Excursus: The Dietary Habits of John the Baptist -- 9.3.1.4 Compatibility between the Parable, Interpretation and Wisdom Saying -- 9.3.1.5 Self-referentiality: Luke 7.31â35 as a Saying of John -- 9.4 Conclusion -- Chapter 10 Coherence and Distinctness: EXPLORING THE SOCIAL MATRIX OF THE DOUBLE TRADITION -- 10.1 Methodological Considerations -- 10.2 Exemplary Analysis: Household Roles -- 10.2.1 Rupture Between Generations â and a New House of the âFatherâ -- 10.2.2 Slaves in the Household of God: Models for (Particular) Followers -- 10.3 Conclusion -- 10.3.1 Coherence and Distinctness -- 10.3.2 Lukeâs Access to the Traditions -- 10.3.3 Prospects
Chapter 11 Taking our Leave of MarkâQ Overlaps: MAJOR AGREEMENTS AND THE FARRER THEORY -- 11.1 What Are the Mark-Q Overlaps? -- 11.2 What Is the Problem? -- 11.3 Major and Minor Agreements -- 11.4 The Degree of Mark in Lukeâs MarkâQ Overlap Passages -- 11.5 The Direction of Dependence -- 11.6 Conclusion -- Chapter 12 The Gospel of Luke as narratological Improvement of Synoptic pre-texts: THE NARRATIVE INTRODUCTION TO THE JESUS STOR -- 12.1 Introduction -- 12.2 Qâs Parallel Beginning to Markâs Gospel -- 12.3 Methodological Considerations -- 12.3.1 The Synoptic Improvement Model -- 12.3.2 Narratological Analysis -- 12.3.3 A Synoptic Analysis of Mark 1.1â8 // Matt 3.1â12 // Luke 3.1â20 -- 12.4 Conclusion -- Chapter 13 Does Dating Luke-Acts into the Second Century Affect the Q Hypothesis? -- 13.1 Dating Lukan Materials -- 13.2 Canonical Luke and Marcionâs Evangelion -- 13.3 A âMarcionite Solutionâ to the Synoptic Problem? -- 13.4 Concluding Observations -- Chapter 14 Marcionâs Gospel and the Synoptic Problem in Recent Scholarship -- 14.1 Introduction -- 14.2 Prolegomena -- 14.3 Marcionâs Gospel as the Key to Solving the Synoptic Problem -- 14.4 Marcionâs Gospel as Relevant, but not Determinative, for the Synoptic Problem -- 14.5 Conclusion -- Author Index -- Subject Index -- Index of References
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Bible